Eksplorasi Nematoda Entomopatogen pada daerah Rhizosfer Tanaman Hortikultura di Desa Rumahtiga dan Wayame Kota Ambon - Rikki Bahagia Sembiring; Aminuddin Umasangaji; Muhammad Riadh Uluputty (JURNAL PERTANIAN KEPULAUAN, 2023)
Biological control of several types of pests and diseases of horticultural vegetables and plantations qualitatively and quantitatively. The results of the study found the genus Steinernema spp in every type of plant in both sample villages. The highest NEP population density was found in Negeri Rumahtiga in eggplant plants with an average population of infective juvenile phase NEP (661.8 heads) and the lowest average population is found in chili plants (228.8 heads). The highest average population in Wayame village was found in tomato plants (425.8 ji NEP), while the lowest average was in chili plants (245.0 ji). In addition, the results of various analyses of population density showed a real influence on entomopathogenic nematodes in Rumahtiga Country, while in Wayame village there was no real effect